Mesoporous Thin Films of TiO2 on Attenuated Total Reflection Crystals. An In Situ Fourier-Transform Infrared Study of the Kinetics and Equilibrium of Adsorption and Photocatalysis of Carboxylic Acids - Roncaroli, Federico (2013)
Highly organized titanium dioxide (TiO2) mesoporous thin films were deposited directly on silicon attenuated total reflection (ATR) crystals by dip-coating, submitted to two different thermal treatments, and characterized by ellipsometric porosimetry analysis (EPA), X-ray diffraction, and electron microscopy. The kinetics and equilibrium of the adsorption of oxalic acid as well as their photocatalytic efficiency were studied in situ by Fourier transformed infrared spectroscopy (FTIR-ATR). The spectral properties and the Langmuir constants of the detected surface complexes resemble those previously found in TiO2 Degussa P25 and anatase particulate films. The photocatalytic activity for the oxidation of oxalic acid was found to be similar to the corresponding one for Degussa P25. The kinetics of adsorption of oxalic acid follows a pseudo-first-order behavior. The pseudo-first-order rate constants show a linear relationship with the oxalic acid concentration. Adsorption (ka) and desorption rate constants (kd) were obtained. The ka values were analyzed in relation to the pore and neck sizes, accessible volume, thickness, and film area. The film area affects strongly the kinetic parameters, while no clear dependence on the thickness value was observed. When the film area is taken into account, adsorption rates on mesoporous films are appreciably larger than on particulate films. Thus, enhanced adsorption rates make mesoporous films better candidates as photocatalysts. The difference is interpreted in terms of a reduced tortousity in the ordered mesoporous films, probably due to their regular spatial order. It is also concluded that sensors and catalysts based on mesoporous films should respond faster than those based on conventional films.